Penerapan Metode Teams Games Tournaments Dipadukan Dengan Ajaran Catur Naya Sandhi Untuk Meningkatkan Aktivitas Dan Prestasi Belajar Pendidikan Agama Hindu Dan Budi Pekerti Siswa Kelas VII SMP Mutiara Singaraja Tahun Pelajaran 2023/2024 - Susanti, Ida; Mastiningsih, Ni Nyoman; Karismayanti, Komang Tari (Jurnal Widya Sastra Pendidikan Agama Hindu, 2024)
Based on observations of the activity and learning achievements of the students of the secondary school Mutiara Singaraja can be categorized as still very low. Seeing from the phenomenon above, the study aims to improve the student's learning activity and performance by trying to apply the TGT method. (Teams Games Tournaments). The subject of the study is a student of the Seventh Grade of the Imperial Mutiara High School in the 2023/2024 school year. The study used the TGT (Teams Games Tournaments) method in Hindu and Buddhist religious education subjects. In this study, the researchers set targets in average class (M) 80, absorption (DS) 80%, learning intensity (KB) 80 and student activity 80%. It is seen from the results of this study that the application of TGT (Teams Games Tournaments) can improve student activity and performance in Hindu Religion Education and Budi Pekerti subjects. This result is shown by the increase in learning activity in Cycle I = 55.6% and in the Cycle II to 82.3% student learning performance is also increased, i.e.: in the cycle I average (M) 76.65, Absorption Power (DS) 76,65 and classical learning intensity of 93.54%. From the results of the research that has been achieved this can be implemented by recommending to Hindu Religion Teachers all, the specialty of Religion teachers to apply the method TGT (Teams Games Tournament) as an effort to improve the quality and quality of Education of students in the field of Hindu Education. Keywords: Teams Games Tournaments, Naya Sandhi Chess, Learning Activities, Learning Achievements